PENGEMBANGAN MODEL PEMBELAJARAN MULTIMEDIA INTERAKTIF DALAM PEMBELAJARAN EKOSISTEM PADA MATA PELAJARAN BIOLOGI - MARLINDOAMAN SARAGIH (LP2MTBM MAKARIOZ, 2019)
The purpose of this study was to develop a model of interactive multimedia learning in the learning ecosystem. Interactive multimedia development is expected to be used as a model for students learning biology Junior High School (SMP). The research was conducted in junior Labschool Jakarta. The method used is the method of development (Research and Development) by Borg and Gall. Development is done through the stages of design, production, evaluation, and revision of the product. The design process begins with the collection of material and other supporting components. The production process is a process all colected together in a product and then become the initial product. The evaluation process consists of product: material expert, media expert, small group testing, major field trials, field trials and operational. The trials results are used to revise the product. 63.3 Acquisition of initial test scores and final test score was 84.5. The results of these tests indicate that there is a significant difference between early test scores and student’s final test. The whole everages showed good jugment. It can be concluded that learning by using interactive multimedia learning model developed is effective in enchancing the activity and compentence of students.